2017
DOI: 10.1007/s10680-017-9451-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent Mortality Trend Reversal in Russia: Are Regions Following the Same Tempo?

Abstract: After several decades of negative trends and short-term fluctuations, life expectancy has been increasing in Russia since 2004. Between 2003 and 2014, the length of life rose by 6.6 years among males and by 4.6 years among females. While positive trends in life expectancy are observed in all regions of Russia, these trends are unfolding differently in different regions. First, regions entered the phase of life expectancy growth at different points in time. Second, the age- and cause-specific components of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 48 publications
2
28
0
2
Order By: Relevance
“…Survival rates at 4 years in this trial were ranging around 60% and were thus lower. However, local recurrence rates were around 3%, which may indicate that there were more non-cancer related deaths due to a generally lower life expectancy in Russian population (64.7 for males and 76.3 years for females in Russia versus 78.7 for males and 83.4 for females years in Germany) [33,34]. Second, imbalances in the collective with stage III patients in the IORT only group appeared to limit the interpretation of the impact of IORT alone.…”
Section: Discussionmentioning
confidence: 99%
“…Survival rates at 4 years in this trial were ranging around 60% and were thus lower. However, local recurrence rates were around 3%, which may indicate that there were more non-cancer related deaths due to a generally lower life expectancy in Russian population (64.7 for males and 76.3 years for females in Russia versus 78.7 for males and 83.4 for females years in Germany) [33,34]. Second, imbalances in the collective with stage III patients in the IORT only group appeared to limit the interpretation of the impact of IORT alone.…”
Section: Discussionmentioning
confidence: 99%
“…Common indicators to evaluate the second factor include transportation time, appointment waiting time, etc. Nearby medical resources can improve the medical accessibility of local residents, while remote medical resources will reduce the medical accessibility and increase the mortality rate (26,29,30). Adequate local medical resources can improve medical access for local residents and reduce local mortality.…”
Section: Hypothesesmentioning
confidence: 99%
“…Due to Russia's large size and climatic, socio-economic, ethnic and other diversity, both Russian and foreign scientists pay special attention to studying the trends and scales of differences in the level of mortality in a regional context [Vasin, Costello 1997;Shkolnikov, Vasin 1994;Vallin et al 2005;Timonin et al 2017]. Even in Soviet times it was shown that there existed a southwest/northeast mortality gradient in Russia (RSFSR) [Andreev 1979;Shkolnikov 1987] which remains relevant to this day [Timonin et al 2017]. In addition, there is a special "privileged" place on the "mortality map" of Russia of St. Petersburg and especially of Moscow.…”
Section: The Research Was Funded Under the State Support Programs Of mentioning
confidence: 99%